Children's Attitudes towards Inclusion of Visually Impaired Students in Physical Education Classes: Gender Differences - Dagmar Nemček (OVS LLC, 2022)
Study purpose. The study purpose was to investigate gender differences in children's attitudes toward the inclusion of a student with visual impairment in physical education classes. Materials and methods. The study sample comprised 419 able-bodied primary school students in 6th to 9th grade (boys, n=204, mean age 13.23±1.17 years; girls, n=215, mean age 13.08±1.19 years). A modified version of the standardized attitudinal questionnaire CAIPE-R for the inclusion of visually impaired (VI) students was used as a research method. The internal reliability of CAIPE-R was measured using Cronbach's α. The Shapiro-Wilk test was used to assess the normality of sample distribution. The non-parametric Mann-Whitney U-test was used to assess differences between boys and girls, and the Wilcoxon Signed-Rank test assessed differences between general and sport-specific attitudes. Results. Boys presented rather neutral or indifferent (mean scores 3.19, 3.44 points) attitudes, and girls had slightly positive (mean scores 3.59, 3.74 points) attitudes toward inclusive physical education (PE). Girls, compared to boys, expressed more positive general (U=16786, p=0.000) as well as sport-specific (U=16586, p=0.003) attitudes towards the inclusion of the VI student in PE classes. Both groups of children declared more positive general attitudes than sport-specific attitudes towards the inclusion of VI students (boys, Z=-4.230, p=0.000; girls, Z=-3.015, p=0.003). Conclusions. Girls expressed more positive general and sport-specific attitudes towards the inclusion of VI students in PE classes than boys. Boys' attitudes were only neutral or indifferent, and girls' attitudes were only moderately positive. Both genders declared more positive general attitudes towards the inclusion of VI students in PE classes compared to sport-specific attitudes. Taking into consideration the above, to find the most appropriate solutions as regards the inclusion of students with different kinds of disabilities in PE classes, it is necessary to learn more about the attitudes towards inclusion from students, teachers, and school management.